1207 Update on Progress of the Mesenchymal Stromal Cell Trial in Refractory Lupus. (14th December 2022) - Kamen, D; Lim, SS; Ramsey-Goldman, R; Kalunian, K; Mackay, M; Khosroshahi, A; Sheikh, S; Shah, U; Goldmuntz, E; Welch, B; Ishimori, M; Arriens, C; et al.
Abstract : Body: There is a growing interest and use of cellular therapies in almost all fields of medicine. Mesenchymal stromal cells (MSCs) are pluripotent in their ability to differentiate in chondrocytes, adipocytes and osteoblasts. They more recently were reported to have significant immune activity, primarily by producing anti-inflammatory molecules. They can be derived from umbilical cords, adipose tissue and bone marrow primarily. Recent studies have tested their safety and efficacy in immune mediated diseases including graft versus host disease, inflammatory bowel disease and Type I diabetes among others. Reports of uncontrolled trials of MSCs in China suggest safety and efficacy of MSCs as treatment for refractory lupus. Based on encouraging results of a Phase I trial of 6 patients with lupus treated with MSCs, we initiated the first placebo- controlled trial of MSCs to treat lupus patients refractory to standard of care medications. There are nine participating centers across the US. The trial has two cohorts, one receiving low dose MSCs (one million cells/kg) and a high dose cohort of five million cells per kg, given as a one- time infusion. Patients then attend 10 follow-up visits over a year. Primary outcome is a decrease in the SRI of 4 at week 24. Inclusion criteria are patients with confirmed lupus refractory to 6 months of standard of care therapy defined by a SLEDAI of 6 or greater at screening. Exclusions were ongoing use of biologics, pregnancy, active infections, cancer, active CNS lupus or advanced renal disease. The first patient was screened in November of 2018. Patients are randomized with a 2/1 ratio of MSCs/placebo. Cohort 1 consisting of 41 patients was completed in May of 2021. We have infused 10 out of 40 patients in Cohort 2 to this point. Extensive studies of B cell, T cell, monocyte, dendritic cell and PMN number, function and phenotype are being performed. To this point there are no safety signals or concerns with DSMB reviews quarterly. There have been no SAEs attributed to the investigational product. Given the blind of the study, we cannot report on efficacy, though there are a number of participants who met the primary outcome of an SRI of 4 at 24 weeks. COVID had a profound impact on the study due to halting of enrollment for 5 months and a need for video visits due to institutional policies. A significant issue was protocol changes regarding disease activity measures in video visits. Other delays included a designed 12-week safety assessment upon completion of Cohort 1 prior to enrollment in Cohort 2 as well as a staggered start for the first six patients in Cohort 2 requiring a safety assessment by the DSMB chair at week 1 post infusion prior to the screening of the next patient. Conclusions: There is no safety signal between the active treatment and placebo group in either Cohort to this date. Efficacy assessments await completion of the study as the two cohorts are combined for determination of efficacy. COVID has a profound impact on enrollment and management of the study. Results of the validity of assessment of different disease measures via video appointments is being assessed to inform future trials. We believe we will reach our enrollment goal and the study will answer the primary aim of whether MSCs are a potential therapeutic for patients with refractory lupus.